Stellate cells are in utero markers of pancreatic disease in cystic fibrosis - Shih-Hsing Leir; Svyatoslav Tkachenko; Alekh Paranjapye; Frederick Meckler; Arnaud J. Van Wettere; Jenny L. Kerschner; Elizabeth Kuznetsov; Makayla Schacht; Pulak Gillurkar; Misha Regouski; Iuri Viotti Perisse; Cheyenne M. Marriott; et al. (BMC, 2024)
Abstract Background Pancreatic fibrosis is an early diagnostic feature of the common inherited disorder cystic fibrosis (CF). Many people with CF (pwCF) are pancreatic insufficient from birth and the replacement of acinar tissue with cystic lesions and fibrosis is a progressive phenotype that may later lead to diabetes. Little is known about the initiating events in the fibrotic process though it may be a sequela of inflammation in the pancreatic ducts resulting from loss of CFTR impairing normal fluid secretion. Here we use a sheep model of CF (CFTR −/− ) to examine the evolution of pancreatic disease through gestation. Methods Fetal pancreas was collected at six time points from 50-days of gestation through to term, which is equivalent to ~ 13 weeks to term in human. RNA was extracted from tissue for bulk RNA-seq and single cells were prepared from 80-day, 120-day and term samples for scRNA-seq. Data were validated by immunochemistry. Results Transcriptomic evidence from bulk RNA-seq showed alterations in the CFTR −/− pancreas by 65-days of gestation, which are accompanied by marked pathological changes by 80-days of gestation. These include a fibrotic response, confirmed by immunostaining for COL1A1, αSMA and SPARC, together with acinar loss. Moreover, using scRNA-seq we identify a unique cell population that is significantly overrepresented in the CFTR −/− animals at 80- and 120-days gestation, as are stellate cells at term. Conclusion The transcriptomic changes and cellular imbalance that we observe likely have pivotal roles in the evolution of CF pancreatic disease and may provide therapeutic opportunities to delay or prevent pancreatic destruction in CF.